Strategi Pemasaran Sosis Obong Dendra melalui Media Sosial Facebook - Riska Puspita Dewi; Muhammad Iqbal Fasa (Yayasan Literasi Sains Indonesia, 2024)
This study analyzes the methods and techniques of product marketing through social media, with a special focus on its impact on sales and brand awareness. This study takes the example of the business